Autogas in Road Traffic - Štrumberger, Nada; Šekerija, Željko; Peraković, Dragan (Promet - Traffic&Transportation, 2003)
LPG is an international abbreviation for liquefied petroleumgas, i.e. autogas. Today, there are about 5 million vehiclesin the world that use autogas and the number is constantlygrowing. One of the reasons lies in its efficiency which is provenin the 50% lower fuel price and in the lower maintenance priceof the automotive parts! From the ecological aspect, autogas isa much, much lesser polluter which does not let out fumes,lead, solid particles and sulphur oxides into the atmosphere,generating at the same time less carbon dioxide andnon-degradable hydrocarbons. Because of its characteristicsautogas has favourable impact on the engine. The engine durabilityis increased by about 35% compared to petro~ the engineoperates more quietly, the cylinders wear out less, the oil lastslonger in the engine, the durability of the catalyst and thelambda tube is doubled. Complete combustion of the gas-airmixture in the engine cylinders does not result in fuel losses inthe exhaust gases. The exhaust gases are cleaner.